Student’s voices on Kahoot at tertitary level in East Kalimantan - Dedi Rahman Nur (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2021)
The learning experience that motivates students can be created where competence is quantitatively assessed using gamification technology. A survey of students' opinions of gamification was conducted to determine the best practices of its use, the environmental conditions necessary for its success, and the manner in which the application should proceed. The effects of gamification on math achievement were examined using quantitative methods. The Kahoot application was found to be the preferred method of gamification in this study. These 80 English students took part in the experiment and studied at the Department. The findings revealed that adding gamification to the course increased the overall interest of students and boosted the aspirations of students to succeed in the course. This method also has a strong impact on the motivation of students. What this study found was that Kahoot can be used to successfully gamify lessons. In my research, the gamification method led to greater engagement by students.